Responding to the Radical in RIOT Bible. Issue 3 (3rd September 2015) - Blyth, Caroline
Abstract : In response to the RIOT Bible articles by Sandford, Myles, and Wan, I consider what it means to be a 'radical interpreter' of the Bible. Reflecting in particular on the sense of 'rootedness' that the term 'radical' can convey, I explore how each author digs down to the roots of their subject, all the while pushing away from exegetical normativities to produce a reading that is both unconventional and ground-breaking.